Solve for x : 2x^2+4x-16=0

Answers

Answer 1
Answer: 2x^2+4x-16=0\ \ \ /:2\n\nx^2+2x-8=0\n\n\underbrace{x^2+2x\cdot1+1^2}_((*))-1^2-8=0\n\n(x+1)^2-1-8=0\n\n(x+1)^2-9=0\n\n(x+1)^2=9\iff x+1=-3\ or\ x+1=3\n\nx=-3-1\ or\ x=3-1\n\nx=-4\ or\ x=2\n\n\n(*)\ (a+b)^2=a^2+2ab+b^2



2x^2+4x-16=0\ \ \ /:2\n\nx^2+2x-8=0\n\na=1;\ b=2;\ c=-8\n\n\Delta=b^2-4ac\ if\ \Delta > 0\ then\ x_1=(-b-\sqrt\Delta)/(2a)\ and\ x_2=(-b+\sqrt\Delta)/(2a)\n\n\Delta=2^2-4\cdot1\cdot(-8)=4+32=36;\ \sqrt\Delta=√(36)=6\n\nx_1=(-2-6)/(2\cdot1)=(-8)/(2)=-4;\ x_2=(-2+6)/(2\cdot1)=(4)/(2)=2
Answer 2
Answer: in order to solve it, we need find the zero of the polynomial.

we find the zero of the polynomial by splitting the middle term method

2x2 -+ 4x - 16

= 2x2 + 8x - 4x -16

= 2x( x + 4)- 4(x + 4)
= (2x-)(x+4)

we find the zeroes of the factors

experimentally we find two values, 2 and -4.

Thus, values of x are 2 and -4


Related Questions

What multiplies to 42 and adds to -27
Which of the following statements is true?A) Two similar triangles must be congruent.B) Two congruent triangles must be similar.C) Two triangles having ye same area must be congruent.D) Two triangles having the same perimeter must be similar.
The sales tax in a city is 8.8% and an item costs $63 before tax How much tax would you pay on that item?
Simplify a - {b - [c - (d - e) - f] - g}.
A solid metal sculpture in Kamila’s backyard is in the shape of a sphere and has a radius of 6 inches. She wants to have it melted and made into small solid cones. She would like the cones to each have a diameter of 6 inches and a height of 9 inches. With these dimensions, how many cones can be made from the metal sphere? In your final answer, include all formulas, equations, and calculations necessary to determine how many cones can be made.

Which step should be completed first in the following problem 4(27÷3²)

Answers

Answer:

Step-by-step explanation:

We have to use BPEMDAS Order of Operations:

B - Brackets

P - Parenthesis

E - Exponents

M - Multiply

D - Divide

A - Addition

S - Subtraction

We use this order left to right. Since we have parenthesis, we look at that first. Inside, we have division and exponents. Since exponents come first, we have to evaluate 3² first.

Answer:

square the 3

Step-by-step explanation:

In the order of operations, you must do the exponent inside the parentheses first, so the first step is:

4(27 ÷ 3²) =

= 4(27 ÷ 9)

Answer: square the 3

draw an array to show how to arrange 20 chairs into 5 equal rows. Explain what each part of the array represents.

Answers

Since there are 20 chairs and should be arrange into 5 equal rows. So the number of chairs in each row is equal to 20 / 5 which equal to 4. so let x represent a chair in the array. so the drawing should be like:
x x x x
x x x x
x x x x
x x x x
x x x x 

Dion calculated the plane’s time to fly to another country. He calculated the plane flying at a rate of 600 miles per hour . How long will it take the plane to travel 6,300 miles?

Answers

Answer: 10.5h

Step-by-step explanation:

All we have to do is divide the number of miles by the miles per hour:

6300/600=10.5 h

Find 2 consecutive odd integers whose sum is 116

Answers

To find the answer using an equation, use x for the first integer, and use x+2 as the second integer. (we add 2 to x because odd numbers are 2 away from each other. You would have to add 2 to an odd number to get the next consecutive odd number).
"sum" means to add, so add the two integers together:
x + x+2 = 116
Combine like terms:
2x + 2 = 116
Subtract 2:
2x = 114
Divide by 2:
x = 57 (first integer)
x+2 = 57+2 = 59 (second integer)
Check: 57+59=116
if you add the numbers 57 and 59 together you get 116

What is the value of x in the equation 4x+8y=40 when y=0.8

Answers

Substitute in 0.8 for y.

4x+8y=40 \n \n 4x + 8(0.8) = 40 \n \n 4x + 6.5 = 40 \n \n 4x = 40 - 6.4 \n \n 4x = 33.6 \n \n x = 8.4 \n \n

The final result is: x = 8.4.

you plug in the y .8 to the8 that is 6.4

them you subtract 40 by 6.4that is  33.6

then you divide that by 4is 8.4

2r-4/r-2 please help

Answers

(2r-4)/(r-2 )\n \n r-2 \neq 0 \n \nr\neq 2\n\n\n(2r-4)/(r-2 ) =(2(r-2))/((r-2) ) = 2 \n \n


2r-4/r-2 = 2(r-2)/r-2 = 2